Hyperammonaemia in V1a vasopressin receptor knockout mice caused by the promoted proteolysis and reduced intrahepatic blood volume - Hiroyama, Masami (Blackwell Publishing Ltd, 2007)
An analysis of arginine-vasopressin (AVP) V1a receptor-deficient (V1aR −/−) mice revealed that glucose homeostasis and lipid metabolism were altered in the mutant mice. Here, we used V1aR −/− mice to investigate whether the deficiency of the V1a receptor, which led to altered insulin sensitivity, affected protein metabolism. The serum 3-methylhistidine levels were increased in V1aR −/− mice under feeding conditions, indicating that proteolysis was enhanced in muscle tissue from V1aR −/− mice. Furthermore, serum amino acid profiling revealed that the amino acid levels, including glycogenic and branched-chain amino acids, were reduced in V1aR −/− mice. In addition, an alanine-loading test showed that gluconeogenesis was enhanced in V1aR −/− mice. Blood ammonia, which is a by-product of amino acid catabolism, was two times higher in V1aR −/− mice without hepatopathy under the feeding and fasting conditions than in wild-type mice. Amino acid profiling also revealed that the amino acid pattern was not typical of a urea-cycle enzymatic disorder. An ammonia tolerance test and an indocyanine green elimination test showed that V1aR −/− mice had lower ammonia clearance due to a decreased intrahepatic circulating blood volume. Metabolic acidosis, including lactic- and keto-acidosis, was not observed in V1aR −/− mice. These results provide evidence that proteolysis promotes the production of glucose in the muscles of V1aR −/− mice and that hyperammonaemia is caused by promoted protein catabolism and reduced intrahepatic blood volume. Thus, our study with V1aR −/− mice indicates that AVP plays a physiological role via the V1a receptor in regulating both protein catabolism and glucose homeostasis.